Why small particle fixed dose triple therapy? An excursus from COPD pathology to pharmacological treatment evolution. (January 2022) - Braido, Fulvio; Corsico, Angelo G.; Paleari, Davide; Piraino, Alessio; Cavalieri, Luca; Scichilone, Nicola
Although bronchodilators are the cornerstone in chronic obstructive pulmonary disease (COPD) therapy, the treatment with a single-agent bronchodilator may not provide adequate symptoms control in COPD. The combination of drugs with different mechanisms of action may be more effective in inducing bronchodilation and preventing exacerbations, with a lower risk of side-effects in comparison with the increase of the dose of a single molecule. Several studies comparing the triple therapy with the association of long-acting ß2 agonist (LABA)/inhaled corticosteroid (ICS) or long-acting muscarinic antagonist (LAMA)/LABA reported improvement of lung function and quality of life. A significant reduction in moderate/severe exacerbations has been observed with a fixed triple combination of beclometasone dipropionate (BDP), formoterol fumarate (FF) and glycopyrronium (G) in a single inhaler. The TRILOGY, TRINITY and TRIBUTE studies have provided confirming evidence for a clinical benefit of triple therapy over ICS/LABA combination treatment, LAMA monotherapy and LABA/LAMA combination, with prevention of exacerbations being a key finding. A pooled post hoc analysis of the published clinical studies involving BDP/FF/G fixed combination demonstrated a reduction in fatal events in patients treated with ICS-containing medications, with a trend of statistical significance [hazard ratio = 0.72, 95% confidence interval (CI) 0.50–1.02, p  = 0.066], that becomes significant if we consider reduction in fatal events for non-respiratory reasons (hazard ratio = 0.65, 95% CI 0.43–0.97, p  = 0.037). In conclusion, a fixed combination of more drugs in a single inhaler can improve long-term adherence to the therapy, reducing the risk of exacerbations and hospital resources utilization. The twice a day administration may provide a better coverage of night, particularly in COPD patients who are highly symptomatic. The inhaled extrafine formulation that allows drug deposition in both large and small – peripheral – airways, is the value added.